Biochemical and immunological characterization of the major envelope glycoprotein of bovine leukemia virus. - Devare, S G (1977)
The major envelope glycoprotein of bovine leukemia virus was isolated by lectin-bound Sepharose and DEAE-cellulose column chromatography. This protein was shown to have a molecular weight of about 41,000 and to lack detectable immunological cross-reactivity with glycoproteins of other oncornaviruses. Sera obtained from 100% of cattle examined with clinically diagnosed lymphosarcoma contained high-titered antibody to 125I-labeled bovine leukemia virus glycoprotein, whereas sera from animals in a disease-free herd were antibody negative.